PENGELOLAAN BANGGAI CARDINALFISH (Pterapogon kauderni) MELALUI KONSEP ECOSYSTEM-BASED APPROACH (Banggai cardinalfish (Pterapogon kauderni) Management an Ecosystem-Based Approach) - Samliok Ndobe; Abigail Moore; Al Ismi M. Salanggon; . Muslihudin; Daduk Setyohadi; Endang Y. Herawati; . Soemarno (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2013)
ABSTRACTThe Banggai Cardinalfish (Pterapogon kauderni) or capungan Banggai (often abbreviated as BCF) is a marine fish endemic to the waters around the Banggai Archipelago, caught in large numbers for the marine aquarium trade. The conservation of this endemic species became an international issue, in 2007 the BCF was proposed for CITES listing by the USA and listed as Endangered in the IUCN Red List. The CITES proposal was withdrawn, with Indonesia committed to conserve the Banggai Cardinalfish through a sustainable ornamental fishery approach. The multi-stakeholder Banggai Cardinalfish Action Plan (2007-2012) and other initiatives have aimed towards this goal; however the initiative to secure limited protected status in 2011 failed. Studies during 2011-2012 found many positive developments in the BCF fishery, and if the carrying capacity (stocks and ecosystems) was similar to the early 2000’s, current official exploitation levels should be sustainable. However a stock assessment analysis using FISAT II revealed a high exploitation level (0.5), indicating catches may have reached or possibly exceeded sustainable limits. Survey/monitoring results indicate the endemic population is not in a steady state, with sharp declines in the past decade. There are strong indications that habitat degradation is the main cause of this decline, including over-exploitation of key BCF micro-habitat (sea urchins and sea anemones). Without an effective solution to protect the supporting ecosystem, P. Kauderni will be increasingly threatened with extinction, with or without fishing pressure. The case of the BCF highlights the importance of an ecosystem-based approach to fisheries policy and management.Key words: ecosystem-based approach to fisheries management, Pterapogon kauderni, stockassessment, sustainable ornamental fishery-------ABSTRAKBanggai cardinalfish (Pterapogon kauderni) yang sering disingkat BCF atau capungan Banggai merupakan ikan laut endemik di perairan Banggai Kepulauan dan sekitarnya yang ditangkap dalam jumlah besar untuk diperdagangkan sebagai ikan hias. Kelestarian spesies endemik tersebut menjadi isu internasional dan pada tahun 2007 diusulkan pada CITES oleh Amerika Serikat dan didaftarkan sebagai Endangered pada Red List IUCN. Status terdaftar pada CITES ditangguhkan, namun Indonesia berkomitmen untuk menjamin kelestarian Banggai cardinalfish dengan pola sustainable ornamental fishery. Rencana Aksi Banggai Cardinalfish multi-stakeholder (2007-2012) dan beberapa inisiatif lain bertujuan mewujudkan tujuan tersebut antara lain penetapan status jenis lindung terbatas, namun upaya yang diinisiasi pada tahun 2011 tersebut gagal. Berdasarkan data kajian 2011-2012, banyak perubahan positif dalam perikanan BCF, dan jika daya dukung alam (stok dan ekosistem) masih seperti pada awal tahun 2000-an tingkat pemanfaatan resmi seharusnya sustainable. Hasil kajian menggunakan FISAT II bahwa tingkat pemanfaatan (0,5) tergolong tinggi, dan merupakan indikasi bahwa tingkat pemanfaatan telah pada atau melebihi batas maksimal lestari. Hasil survey/monitoring menunjukkan bahwa populasi endemik tidak pada kondisi steady state dan menunjukkan penurunan tajam dalam dekade terakhir. Terindikasi kuat bahwa penyebab utama penurunan tersebut adalah degradasi habitat, antara lain akibat pemanfaatan lebih mikrohabitat (bulu babi dan anemon laut). Tanpa solusi efektif untuk melestarikan ekosistem pendukung, P. kauderni akan semakin terancam punah, dengan atau tanpa adanya penangkapan. Kasus BCF menunjukkan pentingya pendekatan ecosystem-based approach terhadap kebijakan dan manajemen perikanan tangkap.Kata kunci: ecosystem-based approach to fisheries management, Pterapogon kauderni,pengkajian stok, sustainable ornamental fishery